Serum Inorganic Phosphate and Alkaline Phosphatase Activity in Cold-Exposed Rat - Haque, Md Shahidul; Shima, Zerin Fahmida (TAJ: Journal of Teachers Association, 2011)
To characterize serum constituents in blood in response to cold exposure, we measured serum inorganic phosphate (Pi) and alkaline phosphatase (ALP) levels. After 30 min exposure of cold, the serum Pi and alkaline phosphatase levels were 3.4 ± 0.06 mg/l and 72.33 ± 0.45 μmole/l respectively where as the control levels of these constituents are 3.05 ± 0.03 mg/l and 84 μmole/l respectively. Cold exposure for 30 min induces serum Pi concentration by 11.5 % and decreases ALP levels significantly by 13.9 % compared to control rats. Serum Pi for 1 h and 2 h were 3.8 mg/l and 4.17 ± 0.16 mg/l while ALP levels were 57.33 ± 0.88 μmole/l and 91 ± 1.73 μmole/l respectively in different groups of rats. Cold exposure stimulates serum Pi by 24.6 % and 36.7 % and reduces ALP activity by 31.7 % significantly and without significant change for 1 h and 2 h respectively. Another groups of rats exposed to cold for 4 h had Pi and ALP levels 4.66 ± 0.88 mg/l and 85.66 ± 0.88 μmole/l respectively. Cold exposure similarly stimulates Pi content significantly by 52.8 % without affecting ALP activity compared to the control rather reaches to basal level. Our results demonstrate that Pi and ALP levels in cold-exposed rats are regulated in different ways. doi: 10.3329/taj.v19i1.3162 TAJ 2006; 19(1):13-17